Reactive oxygen species and p47phox activation are essential for the Mycobacterium tuberculosis-induced pro-inflammatory response in murine microglia - Yang, Chul-Su (BioMed Central, 2007)
BACKGROUND: Activated microglia elicits a robust amount of pro-inflammatory cytokines, which are implicated in the pathogenesis of tuberculosis in the central nervous system (CNS). However, little is known about the intracellular signaling mechanisms governing these inflammatory responses in microglia in response to Mycobacterium tuberculosis (Mtb). METHODS: Murine microglial BV-2 cells and primary mixed glial cells were stimulated with sonicated Mtb (s-Mtb). Intracellular ROS levels were measured by staining with oxidative fluorescent dyes [2',7'-Dichlorodihydrofluorescein diacetate (H(2)DCFDA) and dihydroethidium (DHE)]. NADPH oxidase activities were measured by lucigenin chemiluminescence assay. S-Mtb-induced MAPK activation and pro-inflammatory cytokine release in microglial cells were measured using by Western blot analysis and enzyme-linked immunosorbent assay, respectively. RESULTS: We demonstrate that s-Mtb promotes the up-regulation of reactive oxygen species (ROS) and the rapid activation of mitogen-activated protein kinases (MAPKs), including p38 and extracellular signal-regulated kinase (ERK) 1/2, as well as the secretion of tumor necrosis factor (TNF)-α, interleukin (IL)-6, and IL-12p40 in murine microglial BV-2 cells and primary mixed glial cells. Both NADPH oxidase and mitochondrial electron transfer chain subunit I play an indispensable role in s-Mtb-induced MAPK activation and pro-inflammatory cytokine production in BV-2 cells and mixed glial cells. Furthermore, the activation of cytosolic NADPH oxidase p47phox and MAPKs (p38 and ERK1/2) is mutually dependent on s-Mtb-induced inflammatory signaling in murine microglia. Neither TLR2 nor dectin-1 was involved in s-Mtb-induced inflammatory responses in murine microglia. CONCLUSION: These data collectively demonstrate that s-Mtb actively induces the pro-inflammatory response in microglia through NADPH oxidase-dependent ROS generation, although the specific pattern-recognition receptors involved in these responses remain to be identified.